The Influence Of Entrepreneurial Characteristics And Business Environment On The Success Of Culinary MSME Businesses (Case Study Of Rujak Sellers) Percut Sei Tuan District - Sri Rezeki; Desma Erica Maryati; Hommy Dorthy Ellyany Sinaga; Syahnaya Syahnaya (UNIVED Press, 2025)
This study aims to analyze the influence of entrepreneurial characteristics and business environment on the success of Micro, Small and Medium Enterprises (MSMEs) in Percut Sei Tuan District, Deli Serdang Regency. This study uses a quantitative approach with multiple linear regression analysis methods. Data was collected through interviews, observations, and questionnaires that were distributed to 82 MSME actors selling rujak in the region. The results of the study show that partially, the characteristics of entrepreneurship and the business environment have a significant influence on business success. Simultaneously, these two variables have a significant effect on the success of MSMEs. Thus, good entrepreneurial characteristics and a supportive business environment can increase the success of MSMEs in Percut Sei Tuan District. This research contributes to the development of MSMEs in the culinary sector, especially in the managerial aspects and business environment policies.